Residential Real Estate Market in the Context of Local and Regional Development - Artur Myna (Barometr Regionalny)
The aim of the work is to present the relationship between the development of residential real estate markets and local and regional development. It was found that the number of completed dwellings is strongly connected with the value of transactions on residential property markets in cities of over 200 000 inhabitants (confirmation of the theory of the residential real estate market as a “growth machine”). The value of transactions on the residential real estate market in these big cities proved to be strongly correlated with the number of natural persons performing economic activity and the share of persons working in the service sector in voivodships which would indicate regional development. Along with the increase in transactions on the residential real estate market, the demand for construction and renovation of flats and houses increases, as well as for works that cause an increase in the utility value of the property: finishing works, production and assembly of fences, hardening of the area or setting up gardens. The question arises as to whether natural persons performing economic activity do such works mainly in cities with more than 200 000 inhabitants and in suburbanization areas surrounding them (the hypothesis of local development), or the external effects of real estate markets as a “growth machine” have a supralocal range, somehow “leaking” beyond the areas of large cities and suburbanization zones (the hypothesis of regional development). Therefore, in-depth surveys are necessary.